Definieren, Aufwerten, Erzählen: Qualitative Marktforschung und die Etablierung des Mineralwassers als ein alltägliches Konsumgut (1958–2001); Qualitative Market Research and the Establishment of Mineral Water as an Everyday Consumer Commodity (1958-2001) - Michael Zeheter (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– Since the 1950s, mineral water has been a ubiquitous mass consumer commodity in Germany. This was due to higher incomes and changing consumer behaviour, which manifested itself in rising consumption. From 1958 onwards, the mineral water industry surveyed its customers by employing qualitative market research to better understand consumers' views, improve marketing and influence shopping habits. Today, these surveys are valuable sources for exploring consumers' perceptions and the mineral water industry's attempts at improving sales. They reveal the challenges facing the mineral water industry, its successes in defining mineral water as a product category, in enhancing the commodity's status and in narrating an increasingly coherent story about mineral water's virtues.
Keywords: M31; N34; L66; 330; mineral water; market research; marketing; Germany; consumption; soft drinks